PSO-tuned pid sliding surface of sliding mode control for an electro-hydraulic actuator system - Chong, Chee Soon (2017)
It is well known that the control engineering applications are widely implemented in the industrial fields through the assistance of the Electro-Hydraulic Actuator (EHA) system. The EHA system is commonly exposed to the parameter variations, disturbances, and uncertainties, which are caused by the changes in the operating conditions including supply pressure, total moving mass, and friction. Thus, due to the changes and uncertain operating conditions, an optimization to the system’s controller is necessary in order to obtain a more robust system performance. This thesis presents the optimization on the Proportional-Integral-Derivative (PID) sliding surface of the Sliding Mode Control (SMC) scheme by using Particle Swarm Optimization (PSO) algorithm, applied to EHA system particularly for positioning tracking control. The EHA system is modelled according to the theories of the physical law, which taking into account the effect of nonlinearities, uncertainties, and disturbances occurred in the system. A robust control strategy is then formulated based on the control laws of the SMC, where the design of the sliding surface is integrated with the PID controller. The proposed control strategy is designed based on the EHA system that is subjected to the nonlinear characteristics and model uncertainties. Then, the PSO, which is based on the inspiration of the swarming behaviour has been utilized to seek for the optimum PID sliding surface parameters. The conventional tuning technique for the PID controller, which is known as Ziegler-Nichols (ZN) has been used to obtain the initial value of the PID sliding surface. Finally, the comparison has been made by applying the obtained parameters through the ZN and PSO tuning technique to the conventional PID controller and the PID sliding surface of the SMC. The findings indicate that the proposed robust SMC with PSOPID sliding surface is preserved to ensure the actuator robust and stable under the variation of the system operating condition, which produce 26% improvement in terms of robustness characteristic that gave a better positioning tracking performance and reduced the controller effort as compared to the conventional PID controller.